Analisis Karakter Intelektual pada Siswa Sekolah Menengah Pertama (Tarbiyah Suska Conference Series, 2022)
This study aims to determine and analyze the intellectual character of junior high school students. Intellectual character is measured and analyzed through intellectual values ​​which are indicators of the formation of intellectual character in students, such as (1) curiosity; (2) open-mindedness; (3) intellectual courage; (4) intellectual thoroughness; and (5) attentiveness. This research is a descriptive research with survey method. The data collection technique uses a rating scale. Data were analyzed descriptively quantitatively. This research was conducted on 212 grade VIII students at SMP N 1 Sleman. The selection of samples selected by purposive sampling. The results showed that the intellectual character of students was in the moderate category, which was 37.26%. The intellectual character of students, such as curiosity, was achieved by 57.93%. The intellectual character of students, such as open mindedness, was achieved as much as 74.85%. The intellectual character of students, such as intellectual courage, was achieved as much as 63.74%. The intellectual character of students, such as intellectual thoroughness, was achieved as much as 64.96%. Students' intellectual character, such as attentiveness, was achieved as much as 71.46%.